Demonstration and evaluation of hemoglobin and hematocrit testing as support services in preparing elite swimmers for serious competition - Busch, James Douglas (My University, 1982)
These studies demonstrated and evaluated the usefulness of hemoglobin concentrations (Hb gm%) and hematocrit percentages (Hct %) in the preparation of elite swimmers for serious competition. Study 1 monitored Hb and Hct levels of nine male swimmers during two months of hard training, tapering, and post-competition rest. Study 2 monitored Hb and Hct levels of the 18 male and 19 female members of the 1978 Commonwealth Games Swimming Teams during maintenance training before competition. Weekly variations were observed during hard training in Study 1. Reduced work load and/or coach determined iron supplementations seemed to increase Hb and Hct levels in most athletes. It was concluded that Hb and Hct screening is a feasible and beneficial support service in the preparation of elite swimmers for competition. For a limited number of individuals more extensive services are required.
Keywords: Hemoglobinometry; Swimming Training; Hematocrit